Pengaruh Profitabilitas, Leverage Dan Pertumbuhan Penjualan Terhadap Tax Avoidance Di Masa Pandemi Covid-19 - Ayu Sundari; Nyimas Wardatul Afiqoh (Universitas Muhammadiyah Gresik, 2022)
This research aims to empirically examine the effect of profitability, leverage and sales growth on tax avoidance. By using 42 samples of financial statements at Manufacturing Companies in the Consumer Goods Sub-Sector listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2020. Sampling uses the purposive sampling method. Data collection techniques using secondary data. The test is carried out using multiple linear regression using SPSS 24. The results of this research show that profitability has no effect on tax avoidance, leverage has no effect on tax avoidance, and sales growth has no effect on tax avoidance.